Severe noncardiogenic pulmonary edema after cardiopulmonary bypass: Case report - Zeng, Jianfeng; Li, Yongxing; Liu, Jing; Li, Li (Heliyon, 2023)
Lung injury is a common complication after cardiopulmonary bypass (CPB). However, cases of noncardiogenic pulmonary edema in which the patient ultimately requires extracorporeal membrane oxygenation (ECMO) support are uncommon. A 54-year-old man was admitted to the hospital with shortness of breath after activity and paroxysmal dyspnoea at night for 3 months. Infective endocarditis and acute heart failure were diagnosed. The patient underwent emergency surgery including aortic valve replacement, mitral valve replacement, tricuspid valve repair, and ventricular septal defect correction. It's noteworthy that the patient experienced significant pulmonary edema during the surgery and within 8 hours postoperatively, with over 3000 mL of yellow-clear fluid aspirated from the trachea and bronchi. The patient eventually recovered through ECMO V–V mode treatment. Inflammatory markers were markedly elevated during the perioperative period, and blood smear revealed Gram-positive bacterial infection. Blood NGS testing detected Streptococcus pneumoniae infection. Despite various factors contributing to the patient's pulmonary edema, it is hypothesized that the edema is related to uncontrolled inflammatory response and cytokine storm. Therefore, when significant pulmonary edema occurs during surgery, swift and decisive actions are necessary to avoid missing the optimal rescue window. If required, the use of ECMO is an effective final treatment option.